Development of an educational solar tracking parabolic dish using raspberry pi - Rahimoon, Asif Ahmed; Soomro, Dur Muhammad; Abdullah, Mohd Noor; Soho, Izhar Ahmed; A. Soomro, Shafique; Ali, Syed Nawaz
Renewable energy systems have become compulsory topic of study for the students of energy generation field due to development of new energy extraction tools. This research presents the development & testing of dual axis educational parabolic solar dish tracker using Raspberry pi controller to test moderate temperature application for institutional and demonstration purposes. The parabolic dish solar collector consists of 4×4ft 2 stainless steel frame, aluminum polished reflecting surface, raspberry pi 3 controller and a closed loop tracking system. The tracking system comprises electro-mechanical components such as a control box, a 12V DC motor, a 12V power window motor, a photo sensor module, a gear box and two thermocouples. This prototype is compact and portable. The unit has been used in applied thermal science courses, such as renewable energy as a demonstration unit in Karachi, Pakistan. This type of activity serves to enhance the students' understanding of renewable energy sources and energy conversion processes. The feedback from the students was very positive and they feel that such apparatus has enhanced their learning of renewable energy and heat transfer concepts.